Incomplete lateral elbow dislocation in children: A report of two cases (Indian Journal of Case Reports, 2019)
Lateral elbow dislocation is an uncommon injury and more so in pediatric age. Most of the elbow dislocations in children and adults are either posterior or posterolateral. Lateral elbow dislocation cases in the literature are limited to anecdotal reports or few cases in large series of elbow dislocation. Out of two described variants, complete and incomplete dislocation, most of the reported cases are of the complete type. Incomplete lateral elbow dislocation thus is a rare injury. Here, we report the case series of two cases of an incomplete variant of lateral elbow dislocation of the left side in nine and eleven year old male children. The cases were successfully managed with closed reduction and the functional outcome measured by the Mayo Elbow Performance Score (MEPS) was excellent till minimum follow-up of ten and fifteen months respectively.